Coro Criativo: uma pesquisa-ação sobre a criação musical na prática coral - Andrade, Klesia Garcia (2019)
Anchored in the qualitative approach and theoretical-practical assumptions of action research, this study has as general aim to understand what dimensions of music training can be worked from a pedagogical action that promotes creativity and involves experiences of musical creation in the choir‟s context. Among the various possibilities of teaching and learning music, the choral practice is consolidated as a relevant modality, attending different generational groups and sociocultural contexts, besides presenting itself as an accessible, collective activity and in a context in which musical execution is generally predominant. The proposed study extends the discussions about this practice, having the promotion of creativity and creation as the guiding thread of the musical-educational process. The theoretical discussion articulates the perspectives of the psychology of creativity and musical education, considering the musical creation from the contemporaneity proposals. In this perspective, it is understood that the human being possesses a certain degree of creative abilities that with favorable conditions and mastery of appropriate techniques, can be improved, disagreeing with the idea that creating requires talent or special abilities. The action research had as an empirical field the Extension Project of the Federal University of Pernambuco (UFPE) “CAp Sings: Musical Education and Choral Practice”, developed at Colégio Aplicação (CAp) from UFPE. The participants directly involved with the empirical field were students and teachers from CAp, graduates in music and I, as general coordinator of the action extensionist, regent and researcher. The intervention process was organized in two stages: the first, the consolidation of choral practice, from August, 2016 until April, 2017; and the second, of creative character, from April, 2017 until November, 2017. Through games, sound exploration and group conversations, the participants were encouraged to propose ideas, resulting in the collective creation of the play “Around Love”. The data analysis reveals the re-signification of choral practice, with emphasis on four dimensions of music training – aesthetics, collaborative, cognitive and affective, and criticism – as well as limitations in the aspect of the representational dimension. The implementation of the musical-educational process based on the promotion of creativity and creation points to the importance of the acquired knowledge by the participants in many sociocultural contexts, evidencing that the act of creating consists in re-elaboration of seized elements and in the balance between convergent and divergent thoughts. The developed action research provided the foundations for the design of the Creative Choir, a comprehensive proposal of choral practice that includes musical creation.